2013
DOI: 10.1353/aad.2013.0028
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Children’s ASL Classifier Production: A Multicomponent Intervention

Abstract: The Authors examined classifier production during narrative retells by 10 deaf and hard of hearing students in grades 2-4 at a day school for the deaf following a 6-week intervention of repeated viewings of stories in American Sign Language (ASL) paired with scripted teacher mediation. Classifier production, documented through a multiple-baseline-across-participants design, was followed by visual analysis and calculation of the percentage of non-overlapping data (Scruggs, Mastropieri, & Casto, 1987). Following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…Other researchers have focused their attention on the use of ASL modeling as a tool for intervening on ASL proficiency, including both using ASL narratives and modeling features of ASL during instruction. These studies have found that opportunities to engage in repeated viewings of ASL narratives has potential to supply d/hh students who sign with ASL language models [33] and that this in turn may support the development and increased use of more advanced ASL linguistic structures [24]. These studies suggest that access to ASL linguistic models may be supportive of linguistic development.…”
Section: American Sign Language Development and Instructionmentioning
confidence: 90%
See 2 more Smart Citations
“…Other researchers have focused their attention on the use of ASL modeling as a tool for intervening on ASL proficiency, including both using ASL narratives and modeling features of ASL during instruction. These studies have found that opportunities to engage in repeated viewings of ASL narratives has potential to supply d/hh students who sign with ASL language models [33] and that this in turn may support the development and increased use of more advanced ASL linguistic structures [24]. These studies suggest that access to ASL linguistic models may be supportive of linguistic development.…”
Section: American Sign Language Development and Instructionmentioning
confidence: 90%
“…Because our knowledge of and discourse around ASL has changed dramatically in recent years, this review focuses only on the research published on this topic within the last 20 years. The research in this area covers a wide range of methodologies, including qualitative studies [23] and single case design research [24,25], as well as larger quantitative group studies [3,[26][27][28][29] and quasi-experimental studies [30,31]. Currently, there are no instances of direct replication or extension of studies in this area, which limits the ability to create more generalizable research-based conclusions about the role of ASL in literacy development and acquisition.…”
Section: American Sign Language Development and Instructionmentioning
confidence: 99%
See 1 more Smart Citation
“…We review these studies in detail below. All of these studies (Beal-Alvarez & Easterbrooks, 2013; Cannon et al, 2010; Golos & Moses, 2011; Guardino, Cannon, & Ebherst, in press; Mueller & Hurtig, 2010) except one (Golos, 2010) embedded live adult mediation before or during the repeated viewings. Repeated viewings without mediation (Beal-Alvarez & Easterbrooks, 2013; Golos, 2010) were compared with repeated viewings with varied levels of scripted teacher (Beal-Alvarez & Easterbrooks, 2013; Golos & Moses, 2011) and parent (Mueller & Hurtig) mediation.…”
Section: Evidence-based Practices (Ebps)mentioning
confidence: 99%
“…The combination of inadequate sign language models, paired with a lack of evidence-based instructional strategies for teaching sign language, results in sign language, English, and reading delays for children who are D/HH. Specific instruction aimed at the development of fluent sign language skills may lead to improved sign language skills for students (Beal-Alvarez & Easterbrooks, 2013; Cannon, Fredrick, & Easterbrooks, 2010; Golos, 2010; Golos & Moses, 2011; Mueller & Hurtig, 2010). In turn, improved language skills may set the stage for better reading outcomes for children who are D/HH.…”
mentioning
confidence: 99%